Education on Providing Supplementary Food to Prevent Stunting in Magei Village, West Misool Distrik, Lilinta Health Center Working Area, West Papua, Indonesia - Fatimah; Nompo, Rifki Sakinah (Indonesian Community Empowerment Journal, 2024)
Stunting is a chronic nutritional problem characterized by a child's height below the standard for his age. Stunting can be caused by various factors, one of which is suboptimal feeding. Education on providing additional food is one of the efforts to prevent stunting. This community service activity aims to provide education about providing additional food to prevent stunting to mothers in Magei Village, West Misool Distrik, Lilinta Health Center Working Area. This activity was carried out from November 1st to 2nd, 2023, involving 86 mothers. Education is provided through lectures and discussions. The material presented includes the meaning of stunting, the factors that cause stunting, and the importance of providing additional food. Participants are also given practice in making additional nutritious food. The results of the activity show that mothers in Magei Village have a good understanding of stunting. After participating in the activity, mothers were also more motivated to provide additional nutritious food to their children.